Opbygning af korpsånd i en dansk bataljon – et casestudie - Lennart Schou Jeppesen (Scandinavian Journal of Military Studies, 2023)
In recent years, there has been a renewed interest in esprit de corps in the Danish Army. Many units have actively worked with enhancing their esprit de corps. Only to a very limited extent, can there be found guidance and support of this work in the military research literature or in the Armed Forces’ guidelines, regulations or doctrine. This article seeks to investigate ways to work with the promotion of esprit de corps through a single case study at a Danish battalion. Data were collected respectively at a management seminar and three months later by interviewing managers in the unit. The study shows how the management group in practice has worked to promote the spirit of the corps in the battalion. They have done so, this study argues, by focusing on three central efforts: 1. Creating a common narrative that embraces the history, values and transformation of the soldiers, 2. Tying the management group together and create leadership power and inspiration 3. Accepting unit differences. This study can be used as inspiration for those who want to work with the promotion of esprit de corps. Abstrakt I de sidste år har der været en øget opmærksomhed på korpsånd i hæren. En opmærksomhed der har fået flere enheder til aktivt at opbygge og fremme korpsånd. Kun i meget begrænset omfang kan der søges vejledning og støtte til dette arbejdet i den militære forskningslitteratur eller i Forsvaret vejledninger, bestemmelser eller doktrin. Denne artikel søger at undersøge, hvordan der kan arbejdes med korpsåndsfremme gennem et single casestudie ved en dansk bataljon. Data blev indsamlet ved henholdsvis et ledelsesseminar og tre måneder senere ved interviews af ledere i enheden. Studiet viser, hvordan ledelsesgruppen rent praktisk har arbejdet med at fremme korpsånden i bataljonen gennem målrettet arbejde med tre centrale indsatser: 1. At skabe en fælles fortælling, der rummer både historien, værdier og transformationen af soldaterne. 2. Binde ledelsesgruppen sammen, skabe ledelseskraft og inspiration. 3. At acceptere og arbejde med enhedsforskelle. Studiet kan med fordel anvendes af andre, der vil arbejde med korpsåndsfremme. Nøgleord: Korpsånd; samhørighed; lederskab; militær ledelse